Estimation of Harvested RF Energy Based on Survey of Ambient RF Power for Optimized Rectifier Design. (30th November 2022) - Arpanutud, Kirote; Tontisirin, Sitt; Chudpooti, Nonchanutt; Chalermwisutkul, Suramate
Abstract : This paper presents estimation of harvested RF energy by means of measurement survey and rectifier circuit simulation. The survey was done in an indoor environment in Bangkok, Thailand using a low-cost in-house developed measurement system. From the survey, channel power distribution of a signal with 950 MHz center frequency and 20 MHz bandwidth was created. The maximum time averaged channel power is -7.6 dBm whereas the mean value with maximum signal statistic is -11.1 dBm. A single stage rectifier is simulated with 5 different nominal values of RF input power which is used to optimize the rectifier for maximum RF-to-DC power conversion efficiency. The rectifier composes a Schottky diode, a matching network and a simple load consisting of a resistor and a storage capacitor. Parameters of the simplified LC matching network have been varied to match the rectifier's input impedance to 50 Ω for various nominal values of the RF input power. In addition, the load resistance was varied according to the nominal RF input power for an optimal power conversion efficiency of the rectifier. The rectifier delivers the highest harvested RF energy with a nominal RF input power of -9 dBm which is a value between the maximum and the mean values from the survey. The DC energy converted from ambient RF energy by the rectifier can be estimated. With this information, it can be assessed what type of applications based on available RF energy can be applied for the test area. This rectifier optimization strategy can be applied to any kind of RF signal since it is based on actual measurement results. Moreover, the proposed rectifier can be designed for reconfigurability regarding nominal RF input power at the location of interest by varying the matching network parameters and the load resistance. In practical applications, the reconfigurable rectifier can maintain a high level of power conversion efficiency over a wide range of RF input power. This can be done by optimizing the rectifier's input matching network and the load resistance for the highest possible power harvested from the environment where the rectifier is located.